The Black Death and Later Plague Epidemics in the Scandinavian Countries: Perspectives and Controversies - Benedictow, Ole Jørgen (De Gruyter, 2016)
This monograph represents an expansion and deepening of previous works by Ole J. Benedictow - the author of highly esteemed monographs and articles on the history of plague epidemics and historical demography. In the form of a collection of articles, the author presents an in-depth monographic study on the history of plague epidemics in Scandinavian countries and on controversies of the microbiological and epidemiological fundamentals of plague epidemics.